THE CONTRIBUTION OF SCIENTIFIC RESEARCH TO THE DEVELOPMENT OF METHODS FOR THE DEVELOPMENT OF SPEECH CULTURE - Mamatkulova Nilufar Boyzak Kizi (International Scientific and Current Research Conferences, 2024)
This article examines the importance of scientific research in the context of the development of methods for the development of speech culture. She analyzes the main directions and achievements of modern linguistics and psychology in the field of development of communication skills and speech competence. The article highlights the results of research on various aspects of speech culture, such as verbal and non-verbal elements of communication, the influence of cultural and social factors on linguistic behavior, as well as methods and techniques that contribute to the development of effective communication. The prospects for further research in this field and their significance for practical application in education, business and everyday life are also discussed. The author calls for further improvement of the research methodology and the development of new approaches to teaching and developing speech culture, taking into account modern requirements and challenges.